Clinical and Radiologic Characteristics of COVID-19 in Patients With CKD (Iranian Journal of Kidney Diseases, 2020)
Introduction. In this study, we aimed to evaluate the presentation and outcome of COVID-19 in patients with chronic kidney disease (CKD). Methods. We included 43 patients with a past history of CKD and confirmed diagnosis of COVID-19. Patients were evaluated for demographic characteristics, clinical and laboratory data and findings of initial chest computed tomography (CT) and were followed until either death or discharge occurred. Then, study variables were compared based on final outcome and stage of CKD. Results. Mean age ± SD of patients was 60.65 ± 14.36 years; 65.1% were male. Five of 43 patients (11.6%) died on follow-up and the rest were discharged. Disease outcome did not differ across CKD stages (P > .05). More than half of the patients (58.1%) presented with severe disease on admission. Clinical symptoms were similar to those of non-CKD individuals. Mean duration of hospitalization was higher in those who died, although not significant (16.6 ± 8.38 vs. 11 ± 6.26, P > .05). The only hematologic parameter that significantly differed between survivors and non-survivors was lactase dehydrogenase level (P < .05). Ground-glass opacification and reticular pattern were the most frequent patterns on CT and pleural effusion existed in about one-fifth of all patients. A greater lower zone score was noted in deceased patients (P < .05). Conclusion. Patients with CKD are vulnerable to a more severe form of COVID-19 and experience a higher mortality rate than the general population; however, higher CKD stage is not related to worse prognosis or different imaging manifestation compared with lower stage.